Attribution of country level foodborne disease to food group and food types in three African countries: Conclusions from a structured expert judgment study - Sapp, A.C.; Amaya, M.P.; Havelaar, A.H.; Nane, G.F. (2022)
Background According to the World Health Organization, 600 million cases of foodborne disease occurred in 2010. To inform risk management strategies aimed at reducing this burden, attribution to specific foods is necessary.